1986
DOI: 10.1007/bf00269123
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal behavior of anther culture derived plants of rice

Abstract: Cytological examination of anther-culture-derived plants of rice showed that the regenerants were predominantly diploids and haploids. Haploid meiosis indicated that the earlier hypothesis of rice being an ancient polyploid is unlikely. Diploids generally were normal and fertile. The low frequency of polyploids (1.5%) probably was due to rapid regeneration of plants from short term callus cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The DH percentage obtained among green regenerated plantlets is similar (56.4%) to that obtained by Mercy and Zapata (1986). Consequently, flow cytometry helped us to discard non-DH plantlets thereby saving time and resources in in vitro propagation works.…”
Section: Comentario [S3]: Aixo De La Regenracio No Aporta Ressupporting
confidence: 62%
“…The DH percentage obtained among green regenerated plantlets is similar (56.4%) to that obtained by Mercy and Zapata (1986). Consequently, flow cytometry helped us to discard non-DH plantlets thereby saving time and resources in in vitro propagation works.…”
Section: Comentario [S3]: Aixo De La Regenracio No Aporta Ressupporting
confidence: 62%
“…Culture conditions may increase sensitivity of heterochromatic regions in regenerated DH plants for such breaks (Youssef et al 1989). Similar and other chromosomal structural modifications has been mentioned in anther derived plants of many crops such as barley (Mix et al 1978), rice (Mercy andZapata 1986, Mezencev et al 1995), maize (Ting 1985, Lee andPhillips 1987), rye (Linacero and Vazquez 1992) and cabbage (Chiang et al 1989). Plants carrying chromosomal abnormalities are a main source of male-sterility and cytological instability which usually impact the whole breeding program.…”
Section: Category Iii: R2-generationmentioning
confidence: 69%
“…radicola Pers.). In rice (Oryza sativa L.), Mercy and Zapata (1986) found that 2.5% anther culture-derived 2x-plants showed meiotic abnormalities which reduced pollen and spikelet fertilities by 69% and 80%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mix et al (1978) reported abnormal root tip mitosis and chromosome breakage in anther culture-derived barley plants. Mercy and Zapata (1986) Table 1.…”
mentioning
confidence: 99%